An atomic scale study of ultralow friction between phosphorus-doped nanocrystalline diamond films. (June 2015) - Wang, Jianjun; Li, Meng; Zhang, Xuehua; Cai, Xiaolin; Yang, Linfeng; Li, Jinming; Jia, Yu
Abstract: The van der Waals corrected first-principles approach within density functional theory was used to investigate the nanofriction properties of phosphorus-doped nanocrystalline diamond films. Our results demonstrate that substitutional phosphorus atoms can significantly decrease the coefficient of friction between two hydrogenated diamond films, and the doping effects are affected by the interfacial environment. These nanofriction modulations can be elucidated by interfacial charge redistribution induced by doping atoms. Our study presents an electronic level mechanism of the doping effects on friction properties of doped interfaces. Highlights: DFT calculations on the friction properties of P-doped nanocrystalline diamond film. Doping P can significantly decrease friction of hydrogenated diamond film. Effects of doping on friction are affected by the interfacial environment. Redistribution of the interfacial charge is primary cause of the friction change.